Elevated synchrony in Parkinson disease detected with electroencephalography. Issue 5 (2nd September 2015) - Swann, Nicole C.; de Hemptinne, Coralie; Aron, Adam R.; Ostrem, Jill L.; Knight, Robert T.; Starr, Philip A.
<x xml:space="preserve">Abstract</x> Objective Parkinson disease (PD) can be difficult to diagnose and treat. Development of a biomarker for PD would reduce these challenges by providing an objective measure of disease. Emerging theories suggest PD is characterized by excessive synchronization in the beta frequency band (∼20Hz) throughout basal ganglia–thalamocortical loops. Recently we showed with invasive electrocorticography that one robust measure of this synchronization is the coupling of beta phase to broadband gamma amplitude (ie, phase–amplitude coupling [PAC]). Other recent work suggests that high‐frequency activity is detectable at the scalp using electroencephalography (EEG). Motivated by these findings, we tested whether beta‐gamma PAC over sensorimotor cortex, recorded noninvasively with EEG, differs between PD patients off and on medications, and healthy control subjects. Methods Resting EEG was compared from 15 PD patients and 16 healthy control subjects. PD patients were tested on and off medications on different days, in a counterbalanced order. For each data set we calculated PAC and compared results across groups. Results PAC was elevated in the patients off medications compared to on medications (p = 0.008) and for patients off medications compared to controls (p = 0.009). Interpretation Elevated PAC is detectable using scalp EEG in PD patients off medications compared to on medications, and compared to healthy controls. This suggests that EEG PAC may provide a noninvasive biomarker of the parkinsonian state. This biomarker could be used as a control signal for closed‐loop control of deep brain stimulation devices, for adjustment of dopaminergic treatment, and also has the potential to aid in diagnosis. Ann Neurol 2015;78:Ann Neurol 2015;78:679–696